Development and validation of the 14-item intentions toward infidelity scale - Pandey, Kashish (Deviant behavior, 2024)
Infidelity is labeled as an unforgivable betrayal in dyadic relationships. It is essential to understand the intentions of committing betrayal to interpret these behaviors. Previous researchers have given well-elucidated justifications for committing infidelity. However, a new measure of intentions toward infidelity is required because existing measures focus on reasons, attitudes, and justifications rather than directly assessing specific intentions. Additionally, infidelity is a multifaceted phenomenon and a dedicated measure for intentions provides a more accurate and comprehensive understanding of individuals’ likelihood to engage in such behavior. Hence, the present study was conceptualized. The sample comprised 561 adults, 489 university students, and 72 working professionals. Out of the total sample, 189 were males (33.69%) and 372 females (66.31%) aged 18 to 50 years (Mage = 21.23, SDage = 4.44 years). Exploratory factor analysis along with confirmatory factor analysis was conducted to examine the dimensionality and validate the measurement theory of the current scale. The results of the exploratory and confirmatory factor analysis revealed a good fit and suggested intentions toward the infidelity scale as a unidimensional construct. These preliminary results confirm that this construct has the premises to be validated as a reliable instrument for measuring intentions toward infidelity.